Overview of C-2W: high temperature, steady-state beam-driven field-reversed configuration plasmas. (8th October 2021) - Gota, H.; Binderbauer, M.W.; Tajima, T.; Smirnov, A.; Putvinski, S.; Tuszewski, M.; Dettrick, S.A.; Gupta, D.K.; Korepanov, S.; Magee, R.M.; Park, J.; Roche, T.; et al.
Abstract: TAE Technologies, Inc. (TAE) is pursuing an alternative approach to magnetically confined fusion, which relies on field-reversed configuration (FRC) plasmas composed of mostly energetic and well-confined particles by means of a state-of-the-art tunable energy neutral-beam (NB) injector system. TAE's current experimental device, C-2W (also called 'Norman'), is the world's largest compact-toroid device and has made significant progress in FRC performance, producing record breaking, high temperature (electron temperature, T e > 500 eV; total electron and ion temperature, T tot > 3 keV) advanced beam-driven FRC plasmas, dominated by injected fast particles and sustained in steady-state for up to 30 ms, which is limited by NB pulse duration. C-2W produces significantly better FRC performance than the preceding C-2U experiment, in part due to Google's machine-learning framework for experimental optimization, which has contributed to the discovery of a new operational regime where novel settings for the formation section and the confinement region yield consistently reproducible, hot, and stable plasmas. An active plasma control system has been developed and utilized in C-2W to produce consistent FRC performance as well as for reliable machine operations using magnets, electrodes, gas injection, and tunable NBs. The active control system has demonstrated stabilization of FRC axial instability. Overall FRC performance is well correlated with NBs and edge-biasing system, where higher total plasma energy is obtained by increasing both NB injection power and applied-voltage on biasing electrodes. C-2W divertors have demonstrated a good electron heat confinement on open-field-lines using strong magnetic mirror fields as well as expanding the magnetic field in the divertors (expansion ratio > 30); the energy lost per electron ion pair, η e ∼ 6–8, is achieved, which is close to the ideal theoretical minimum.